Wireless predictive text entry system for the handicapped - Seah, Ni Xuan (2022)
Text entry systems can usually be found in digital devices such as computers and smartphones that use “QWERTY” keyboards to interact with it. These text entry type devices are easy to use among the general population, but these text input systems are not easily used by people with disabilities. The main problem with this text entry system is that it makes it difficult for people with disabilities to input text. Ordinary keyboards contain 101 or 104 keys and require large hand movements. Therefore, it is not recommended for people with disabilities to use this ordinary keyboard, especially those with limited hand movement. In this project, a new wireless predictive text entry system is created to help handicaps to simplify their text input process so that they can enter text faster. The predictive text input system will be similar to the T9 text input system keyboard, which means it only has a 3x3 grid arrayment key predictive text input system, and it also allows users to select words without typing the entire word in search box. Then, the user’s selected word will be printed in third applications such as notepad. In addition, input device for this system will be designed to be portable, light in weight, long working hours and user-friendly. The input device will be created same as GUI software which have 3x3 grid arrayment key. In addition, handicaps only use one hand to hold the device and use one finger to interact and typing the text. Single tap method is used for this system which mean user need to press the intersection point of the infrared text entry board for one time, the selected letter will print in search box and using number key to select the word to print in third applications. The prediction system uses the Contains method to search for words in the list box, which means that the user enters a letter in the search box and it will start searching for words that contain the following alphabets.